Trichoderma sp. Mushroom Optimization with the Addition of Biostimulants to Reduce TPH (Total Petroleum Hydrocarbons) Levels in Soil Polluted by Palm Oil Mill Waste - Intan Nurhaliza Pane; Rizki Amelia Nasution (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Benzene and toluene compounds in aromatic hydrocarbons can be found from the results of the liquid waste treatment process of palm oil mills that have the potential to pollute the environment in the soil ecosystem. This study aimed to optimize the fungus Trichoderma sp. by adding biostimulants to reduce TPH levels in soil contaminated with palm oil mill waste. The method used in reducing TPH levels was carried out by gravimetric analysis with the addition of biostimulant concentrations in the form of P0 (control), P1 (Trichoderma sp. 15%), P2 (Trichoderma sp. 15% + 35 gr rice husks), P3 (Trichoderma sp. 15% + 100 gr cow dung), P4 (Trichoderma sp. 15% + 35 gr rice husks + 100 gr cow dung) on 300 gr of soil contaminated with oil palm mill liquid waste, nitrogen content test using the Kjeldahl method, phosphorus content test using Spectrophotometry method, potassium content test using AAS method, and pH test. The results showed that the optimization of the fungus Trichoderma sp. with the addition of 35 grams of rice husk stimulant degraded TPH levels by 64.11%, the addition of 100 grams of cow manure stimulant degraded TPH levels by 66.92%, the combined addition of 35 grams of rice husk stimulant and 100 grams of cow manure showed a degradation of TPH levels by 76.02%, and treatment without stimulants degraded TPH levels by 44.90%. Optimization of the fungus Trichoderma sp. with the addition of stimulants in the form of rice husks and cow manure has a significant impact on the reduction of TPH levels.